Assessment of Muscle Fatigue Associated with Prolonged Standing in the Workplace - Isa, Halim (Occupational Safety and Health Research Institute (OSHRI), Korea, 2012)
Objectives: The objectives of this study were to determine the psychological fatigue and analyze muscle activity of production workers who are performing processes jobs while standing for prolonged time periods. Methods: The psychological fatigue experienced by the workers was obtained through questionnaire surveys. Meanwhile, muscle activity has been analyzed using surface electromyography (sEMG) measurement. Lower extremities muscles include: erector spinae, tibialis anterior, and gastrocnemius were concurrently measured for more than five hours of standing. Twenty male production workers in a metal stamping company participated as subjects in this study. The subjects were required to undergo questionnaire surveys and sEMG measurement. Results: Results of the questionnaire surveys found that all subjects experienced psychological fatigue due to prolonged standing jobs. Similarly, muscle fatigue has been identified through sEMG measurement. Based on the non-parametric statistical test using the Spearman’s rank order correlation, the left erector spinae obtained a moderate positive correlation and statistically significant (rs = 0.552, p < 0.05) between the results of questionnaire surveys and sEMG measurement. Conclusion: Based on this study, the authors concluded that prolonged standing was contributed to psychological fatigue and to muscle fatigue among the production workers.